TECHNOLOGIES FOR THE DEVELOPMENT OF PHYSICAL QUALITIES OF PRESCHOOL CHILDREN - Achilova Soxiba Xamidovna,; Turgunboeva Qizlarxon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes technologies for the development of physical qualities of preschool children. Based on the conclusions drawn, proposals were developed.